ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS SISWA PADA PEMBELAJARAN MENDALAM MELALUI MODEL PROJECT BASED LEARNING (PJBL) - Arofa; Najibufahmi, Muhamad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematical representation ability is an essential skill for understanding, presenting, and communicating mathematical ideas. This study aimed to describe the dominant type of mathematical representation, the level of students' mathematical representation ability, and the characteristics of students' mathematical representation ability in Deep Learning through the Project Based Learning (PjBL) model. This study employed a qualitative approach involving 33 tenth-grade students of class X-4 at SMA Negeri 1 Wiradesa in the 2025/2026 academic year. Data were collected through a mathematical representation test and interviews with six students representing visual, symbolic, and verbal representations. The data were analyzed using descriptive statistics and qualitative analysis of the test and interview results. The findings revealed that verbal representation was the most dominant type, with a percentage of 42.55%, followed by symbolic representation at 38.30%, and visual representation at 19.15%. The level of mathematical representation ability was categorized as high for verbal (87.50) and symbolic (86.11) representations, while visual representation was categorized as moderate (72.22). The characteristics of mathematical representation ability showed that students with visual representation were able to construct histograms using class boundaries, students with symbolic representation were able to correctly apply mathematical symbols, formulas, and procedures, and students with verbal representation were able to explain the solution process in a coherent and systematic manner, indicating that students had gone through the stages of understanding, applying, and reflecting in accordance with the principles of Deep Learning, namely mindful, meaningful, and joyful.